Spirit service : Vodún and Vodou in the African Atlantic world - Montgomery, Eric James; Vannier, Christian, 1975-; Landry, Timothy R. (Indiana University Press, 2022)
"-Eric Montgomery is based in East Lansing, MI -Christian Vannier is based in Flint, MI -Tim Landry is based in Hartford, CT - The editors of this volume are early in their careers but are making clear and valuable contributions to the field. They are rising stars in a field where it is difficult to make a mark, and they are generous in their inclusion of precariously-positioned scholars and docrotal candidates in this work. - As religious systems, Vodún, Vodu, and Vodou share an open adaptability which encourages creativity, experimentation, and integration. This adaptability allows the conversation in this collection to move beyond "Africanness" and "European influences" to instead examine how political economies, histories, ritual practices, and migrations produce and reproduce the spirits and the values and practices that surround them. - The collection will appeal to scholars and students of anthropology, sociology, Atlantic and diasporic history, African studies, Caribbean studies, anthropology of religion, and global studies. While there are few courses which focus particularly on Vodún and Vodou throughout an entire semester, each chapter has been written to appeal to course instructors and to upper-level undergraduates for inclusion in course packets. For this reason, the collection would also appeal to those with a general interest in the topic"--